Morphological characterization of newly developed orangelo (Citrus spp.) hybrids - KUMAR, RAUSHAN; SHARMA, NIMISHA; DUBEY, A K; SHARMA, R M; VITTAL, HATKARI; SANDEEP; MISHRA, GYAN P; SETHI, SHRUTI; SHIVRAN, MUKESH; DEEPAK (The Indian Journal of Agricultural Sciences, 2024)
Present study was carried out during 2021–23 (Ambe and Mrig bahar season) at the research farm of ICAR- Indian Agricultural Research Institute, New Delhi to analyse the morphological diversity of 24 orangelo (Citrus spp.) hybrids and their 4 parents based on 17 quantitative traits such as leaves, flowers, fruits and seed characters. Cluster analysis based on 17 morphological traits divided 28 genotypes of citrus into two main groups. A higher range of variation with average Euclidean distance coefficients ranging from 0.02–0.26 was observed between groups as well as clusters, thereby indicating that genotypes within and among clusters were highly diverse. The PCA for morphological quantitative traits showed that five components leaf lamina length (LLL); leaf lamina width (LLW); LLL: LLW; leaf lamina thickness and pedicel length, of the 17 principal component axis had Eigen-values>1 and all together accounted for over 77.76% of the total variability. Analysing the genetic relationships among the hybrids yielded important insights for potential use in future breeding programmes as valuable sources of desirable traits.